Fall Detection with Depth-Videos - Aslan, Muzaffer; Alcin, Omer Faruk; Sengur, Abdulkadir; Ince, Melih Cevdet (Ieee, 2015)
Elderly people, who are living alone are great risk if a fall event occurred. Therefore automatic fall detection systems are in demand for elderly people. In this paper, a depth based fall detection system is proposed. The proposed method consists of shape based fall characterization and a Support Vector Machine (SVM) classifier. Shape based fall characterization is formed with Curvature Scale Space (CSS) features and Fisher Vector (FV) encoding. According to the results obtained from experimental study, the proposed method has better performance than other methods that were published in literature.
Derinlik-Videolari ile Düşme Tespiti
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Fall decection; Curvature scale space; Fisher vector; Support vector machines